The course of Dandy — Walker syndrome in a child with Edwards syndrome - H. A. Sarkisyan; A. B. Smolyannikova; A. A. Fadeeva; E. I. Shabelnikova; O. I. Savvateeva; A. A. Shakirova; A. B. Chashchukhina (Лечащий Врач)
Background. Dandy – Walker syndrome (Dandy – Walker syndrome) is a combined malformation of the brain, the identification of which may be an indication for expanding the diagnostic search in order to detect other malformations or chromosomal pathologies. It is characterized by dysgenesis of the cerebellar vermis, cystic enlargement of the fourth ventricle and an enlarged posterior cranial fossa, as a result of which the sinuses of the meninges and the cerebellum are shifted. The frequency of occurrence ranges from 1:5000 to 1:25000. Agenesia or hypoplasia of the cerebellar vermis in combination with other malformations of the brain are diagnosed already with screening ultrasound scanning of the fetus, however, the diagnosis of Dandy – Walker syndrome is made only after birth based on the manifestations of this syndrome during neuroimaging and genetic studies. In addition to the above changes in the cerebellum, Dandy – Walker syndrome is associated with hydrocephalus, agenesis of the corpus callosum, and other malformations of the central nervous system. The mechanism of development of hydrocephalus in Dandy – Walker syndrome is due to the blockage of normal spinal blood flow, resulting in defects in the holes of Magendie and Luschka. It is characterized by a wide clinical polymorphism. Basically, the first clinical symptoms are diagnosed already in the neonatal period.Objective. The article presents the course of Dandy – Walker syndrome in a child with trisomy 18 (Edwards syndrome).Conclusion. The unfavorable course of this syndrome is most often associated with the presence of concomitant pathology. The severity of clinical manifestations depends on the variant of the syndrome and the rate of progression of disorders. It is often diagnosed in children with chromosomal abnormalities, which complicates the period of early neonatal adaptation, requires the organization of special care and surgical correction of existing malformations. The presence of an infectious process in children with Dandy – Walker syndrome and chromosomal abnormalities can lead to multiple organ failure and deterioration of the child's condition.